Windswept - "De Villiers, Marq, 1940-" (Toronto)
Includes bibliographical references and index. Wind's mystery and meaning -- Wind's great theater -- The search for understanding -- Wind's intricate patterns -- The art of prediction -- The most furious gale -- An ill wind -- The technology of wind.
Keywords: WINDS.;WEATHER.;VENTS.;TEMPS (M???T???OROLOGIE)